Activation of the Orexin 1 Receptor is a Critical Component of CO(2)-Mediated Anxiety and Hypertension but not Bradycardia - Johnson, Philip L (Nature Publishing Group, 2012)
Acute hypercapnia (elevated arterial CO(2)/H(+)) is a suffocation signal that is life threatening and rapidly mobilizes adaptive changes in breathing and behavioral arousal in order to restore acid-base homeostasis. Severe hypercapnia, seen in respiratory disorders (eg, asthma or bronchitis, chronic obstructive pulmonary disease (COPD)), also results in high anxiety and autonomic activation. Recent evidence has demonstrated that wake-promoting hypothalamic orexin (ORX: also known as hypocretin) neurons are highly sensitive to local changes in CO(2)/H(+), and mice lacking prepro-ORX have blunted respiratory responses to hypercapnia. Furthermore, in a recent clinical study, ORX-A, which crosses blood–brain barrier easily, was dramatically increased in the plasma of patients with COPD and hypercapnic respiratory failure. This is consistent with a rodent model of COPD where chronic exposure to cigarette smoke led to a threefold increase in hypothalamic ORX-A expression. In the present study, we determined the role of ORX in the anxiety-like behavior and cardiorespiratory responses to acute exposure to a threshold panic challenge (ie, 20% CO(2)/normoxic gas). Exposing conscious rats to such hypercapnic, but not atmospheric air, resulted in respiratory, pressor, and bradycardic responses, as well as anxiety-like behavior and increased cellular c-Fos responses in ORX neurons. Systemically, pre-treating rats with a centrally active ORX1 receptor antagonist (30 mg/kg SB334867) attenuated hypercapnic gas-induced pressor and anxiety responses, without altering the robust bradycardia response, and only attenuated breathing responses at offset of the CO(2) challenge. Our results show that the ORX system has an important role in anxiety and sympathetic mobilization during hypercapnia. Furthermore, ORX1 receptor antagonists may be a therapeutic option rapidly treating increased anxiety and sympathetic drive seen during panic attacks and in hypercapnic states such as COPD.